Mindfulness-Based Social Cognition Training (SocialMind) for People With Psychosis: A Feasibility Trial - Mediavilla, Roberto; Muñoz-Sanjose, Ainoa; Rodriguez-Vega, Beatriz; Bayon, Carmen; Lahera, Guillermo; Palao, Angela; Bravo-Ortiz, Maria Fe (Frontiers in Psychiatry, 2019)
Introduction: Difficulties in social functioning are common among people with psychosis. Negative symptoms such as blunted affect or social withdrawal are often linked to these difficulties and worsen real-life outcomes. One important dimension associated with social functioning is social cognition, which refers to the psychological processes that are necessary to perceive, encode, store, retrieve, and regulate social information. Mindfulness-based interventions for people with psychosis are safe and effective in improving anxiety and depressive symptoms; however, no mindfulness-based interventions addressing social cognition have yet been developed. Method: A pilot, single-arm, nonrandomized, noncontrolled feasibility trial is proposed. The main objectives are to assess the tolerability of mindfulness-based social cognition training (SocialMind) and to test the feasibility of a further randomized controlled trial. Results: A final sample of 25 outpatients with schizophrenia spectrum disorders was included. Attrition rate was lower than usual for this population, and most participants completed the training. No adverse effects were identified in terms of hospitalizations, emergency room visits, dissociative and psychotic symptoms, or state of anxiety during the sessions. Conclusion: This is the first implementation of SocialMind, which is the first mindfulness-based social cognition training. It is well tolerated by participants with schizophrenia spectrum disorders, and a further randomized controlled trial is proposed for people who have suffered their first episode of psychosis within the past 5 years. Clinical Trial Registration:www.ClinicalTrials.gov, identifier NCT03434405.